Subject Matter Knowledge of Prospective Mathematics Teachers on Quadratic Functions Using Problem-Based Learning - Sumartini, Tina Sri (Universitas Pendidikan Ganesha, 2021)
Subject matter knowledge is important knowledge possessed by prospective mathematics teachers. In general, this study aims to examine the achievement of Subject Matter Knowledge (SMK) of mathematics teacher candidate students who study with the Problem Based Learning (PBL) model. This study used a mixed-method. The research design used was explanatory sequential design. The population consisted of undergraduate students of the Mathematics Education Study Program.Â The sample used was 80 students of prospective mathematics teachers consisting of 40 students in the PBL class and 40 students in the CL-class. The results obtained were: the achievement of the vocational students of mathematics teacher candidates who studied with PBL was better than those of prospective mathematics teacher students who studied with conventional learning. In addition, from the five indicators, four indicators experienced a high increase and one indicator experienced a moderate increase, namely the indicator of the ability to connect the concept of a quadratic function in everyday life.